STRATEGI MANAJEMEN DALAM MENINGKATKAN DAYA SAING USAHA BATU UKIR DI DESA ALLAKUNG KECAMATAN MARITENGNGAE KEBUPATEN SIDENGRENG RAPPANG - Rahman, Risma; Hamid, Hariyanti; Hardianti (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze management strategies to increase the competitiveness of stone carving businesses in Allakuang Village, Maritengngae District, Sidengreng Rappang Regency. The stone carving business is a leading sector based on local potential and a source of income for the local community, but has experienced a significant decline following the Covid-19 pandemic. This decline in competitiveness is influenced by various factors, both internal such as weak innovation and managerial skills, and external such as limited promotion and competition from imported products. This study used a descriptive quantitative approach with data collection techniques through observation, interviews, and questionnaires distributed to 90 respondents using IBM SPSS Statistics 21.0. The analysis was conducted on seven management strategy indicators, including: internal and external environmental analysis, vision and mission determination, long-term strategy selection and implementation, functional policies, and performance evaluation. The results of the study indicate that all management strategy indicators scored an average of 56%, categorized as "poor." Meanwhile, in terms of competitiveness, indicators such as human resource capability, technology utilization, and product price and quality also fell into the "poor" category, with an average score of 59%. Keywords: Management Strategy, Competitiveness, Carved Stone, Allakuang Villag